Toponimia altomedieval castrense. Acerca del origen de algunos corónimos de España - Rafael Barroso Cabrera; Jesús Carrobles Santos; Jorge Morín de Pablos (E-Spania, 2013)
In the present article the authors treat some relative questions to the Spanish mediaeval military toponymia and his connection with the training of new political units around counties and border marks. From these pages the authors defend the relations of the names of Castille and Catalonia from a system of fortresses on rocks that gave origin to both political entities, as well as the equivalence in origin of the names ‘español’ and ‘catalan’. At the same time, we postulate as a hypothesis the derivation of the name ‘navarri’ from a system of natural defences in the Western Pyrenees.